Cashews - Bassier, Emma (2022)
This book introduces readers to how cashews are grown, harvested, and prepared.--
"4D book!"--Cover.
Includes index.
Ages 4-7
Keywords: Cashew -- Juvenile literature; Cashew nut -- Juvenile literature; Agriculture -- Juvenile literature; Food crops -- Juvenile literature; Cashew nut; Cashew; Cashew; Cashew nut; Juvenile works